Students’ Attitudes Towards Using ChatGPT as a Learning Tool: The Case of the University of Jordan - O. Ajlouni, Aseel; Abd-Alkareem Wahba, Fatima; Salem Almahaireh , Abdallah (International Journal of Interactive Mobile Technologies (iJIM), 2023)
This research aims to examine students’ attitudes toward using ChatGPT as a learning tool using a quantitative approach with a descriptive study design. For data collection, researchers have developed attitude measures that utilize the ABC model, which encompasses three components of attitudes (affective, cognitive, and behavioral). The study was conducted among a random sample of 623 undergraduates who enrolled at the University of Jordan, consisting of 476 females and 147 males. The results of the descriptive statistics indicate that there is a high level of positive attitude toward utilizing ChatGPT as a learning tool. Furthermore, the findings confirm moderate affective and high behavioral and cognitive components of attitudes toward using ChatGPT as a learning tool among undergraduate students. A proportion of respondents (73.2%) agreed on the potential ability of ChatGPT to facilitate the learning process. In comparison, 20.7% of the study participants raised apprehensions regarding the precision of the data produced by ChatGPT, while an equivalent percentage (20.7%) reported feeling uncomfortable utilizing the platform; conversely, 14.6% of those surveyed acknowledged experiencing anxiety when unable to access ChatGPT’s services. The results of this study encourage decision-makers and educators at the University of Jordan to incorporate ChatGPT into curricula and instructional practices, considering student concerns and the risk of misuse.